Liquid Crystals: Development of Glassy Bicontinuous Cubic Liquid Crystals for Solid Proton‐Conductive Materials (Adv. Mater. 4/2017). Issue 4 (January 2017) - Kobayashi, Tsubasa; Ichikawa, Takahiro; Kato, Takashi; Ohno, Hiroyuki
Abstract : Infinite periodic minimal surfaces (IPMS) are unique surfaces with 3D continuity and periodicity. In article 1604429, T. Ichikawa and co‐workers create hydrophilic IPMS by using self‐organization of bicontinuous cubic liquid‐crystalline zwitterions and subsequent glassification. These glassy liquid crystals can incorporate water onto their IPMS while keeping the 3D structures. This study may provide a new strategy for developing solid proton‐conductive materials.